1981
DOI: 10.1136/vr.108.13.277
|View full text |Cite
|
Sign up to set email alerts
|

Significance of atrophic ovaries in livestock production in northern Nigeria

Abstract: In a study of 3000 cattle of different breeds and origin (Bos indicus and Bos taurus) in Northern Nigeria, an overall 22.7 per cent incidence of anoestrus associated with organic genital abnormalities was observed. Of this 19.3 per cent was due to ovarian atrophy. This was observed mostly during the pre-dry and dry seasons, periods of poor and inadequate feed. The average incidence of atrophic ovaries in the exotic breeds (Bos taurus) was 17.1 per cent, while an incidence of 20.4 per cent was observed in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This compares with a figure of 5-2% obtained from milk progesterone in cows up to Day 50 post partum (Bulman & Lamming, 1978). Clinical survey data on zebu from Africa, and from India, have shown that 58-84-8% of functional reproductive failures are attributed to atrophie ovaries and the absence of ovarian cyclicity (Kumi-diaka, Ogwu & Osori, 1981;Rao, 1982).…”
Section: Ovarian Abnormalitiesmentioning
confidence: 74%
“…This compares with a figure of 5-2% obtained from milk progesterone in cows up to Day 50 post partum (Bulman & Lamming, 1978). Clinical survey data on zebu from Africa, and from India, have shown that 58-84-8% of functional reproductive failures are attributed to atrophie ovaries and the absence of ovarian cyclicity (Kumi-diaka, Ogwu & Osori, 1981;Rao, 1982).…”
Section: Ovarian Abnormalitiesmentioning
confidence: 74%
“…A single case of ovarian atrophy and ovarian tumour was noticed. A study in 3000 cattle showed that 19.3% of the anoestrum occurred as a result of ovarian atrophy 17 . The occurrence of tumours in goats has been found low, ranging from 0.8%-7.6% 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Inactive ovaries show no change in the ovary size, which is elastic, without follicles or CL. If the ovaries become small, hard and lack elasticity, then ovarian atrophy has occurred (Kumi-Diaka et al 1981;Van Straten et al 2008). When lactating cows are in a NEB state, the secretion of gonadotrophin releasing hormone and LH is restrained, leading to a shortage of these hormones (Canfield and Butler 1990).…”
Section: Classification Of Anoestrusmentioning
confidence: 99%